Examining the Emergence of Computational Thinking through Unplugged Coding Games in Early Childhood: Evidence from a Multiple Case Study in Indonesia - Fitriyah, Qonitah Faizatul; Asmawulan, Tri; Faza, Atika Tsania; Wafa, Khadijah; Susilo, Taufik Eko (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – Computational Thinking (CT) is widely recognized as a key competency in 21st-century education; however, its implementation in early childhood settings remains predominantly associated with digital technologies, leaving its development in low-resource contexts underexplored. This study aims to examine how CT skills emerge through unplugged coding games in early childhood education and to identify the contextual factors shaping their implementation.Design/methods/approach – This study employed a qualitative multiple case study design across three early childhood education settings in Surakarta, Indonesia. Data were collected through six weeks of non-participatory classroom observations and semi-structured interviews with teachers. Observational data were analyzed using a computational thinking framework, while interview data were examined inductively to uncover enabling and constraining factors.Findings – Findings reveal that unplugged coding games, grounded in concrete materials and play-based activities, facilitate the emergence of core CT skills, including sequencing, decomposition, pattern recognition, abstraction and problem-solving. These skills develop through embodied, collaborative, and iterative play processes, where children actively construct solutions within meaningful contexts. However, teachers tend to mediate these processes implicitly, often without explicitly recognizing or articulating them as CT practices, which may limit pedagogical intentionality.Research implications/limitations – The study is limited to three cases within a single regional context and a relatively short observation period, which may constrain the transferability of findings. Nevertheless, it contributes to the conceptualization of CT as a socially mediated and play-based learning process in early childhood, extending beyond technology-centric approaches.Practical implications – The findings highlight the feasibility of integrating CT into early childhood education through unplugged, play-based pedagogies, offering an accessible and contextually adaptable approach for low-resource settings.Originality/value – This study advances the CT literature by demonstrating that computational thinking can emerge through non-digital, play-based interactions in early childhood contexts, challenging dominant technology-driven paradigms and providing empirical evidence from the Global South to broaden theoretical and geographical representation in the field.Paper type Research paper